Long term impact of industrial effluents on agricultural soil - Sahare, Deepti (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Rapid industrialization affects the environment in different ways by discharging the large amount of effluent as waste water in the surrounding water bodies, causing the serious problems to environment. Due to lack of irrigation water in the present study area canal water was used in which effluents from various industries were being discharged. Four water samples were collected from four locations and three to four replicate analysis was carried out for each sample. Sampling locations were selected after each 0.5 km from discharging points. Collected water samples were analyzed for physico-chemical characteristic, heavy metal and sulphide content. Five soil samples were collected from different fields and three to four replicate analysis was carried out for each samples. Impact of effluent on agricultural soil, is mainly due to the presence of high nutrient contents (Nitrogen and Phosphorus), high total dissolved solids and other constituents such as heavy metals, which are added to the soil over time. Wastewater can also contain salts that may accumulate in the root zone with possible harmful impacts on soil health and crop yields. The leaching of these salts below the root zone may cause soil and groundwater pollution. Prolonged use of saline and sodium rich wastewater is a potential hazard for soil as it may erode the soil structure and effect productivity. This may result in the land use becoming non-sustainable in the long run. Wastewater induced salinity may reduce crop productivity. The net effect on growth may be a reduction in crop yields and potential loss of income to farmers. Canal water was containing high COD, BOD values and higher heavy metal content and the soil irrigated with this water was showing the poor status of the nutrients and high contamination of heavy metals. The present study was to evaluate the various adverse effects on the soil characteristics irrigated with discharged water. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->